The Proteome and Secretome of Cortical Brain Cells Infected With Herpes Simplex Virus - Hensel, Niko; Raker, Verena; Förthmann, Benjamin; Buch, Anna; Sodeik, Beate; Pich, Andreas; Claus, Peter (Frontiers in Neurology, 2020)
Infections of the brain with herpes simplex virus type 1 (HSV-1) cause life-threatening Herpes simplex encephalitis (HSE) characterized by viral replication in neurons and neuro-inflammation including an infiltration of peripheral immune cells. HSV-1 reprograms host cells to foster its own replication and for immune evasion, but eventually the immune responses clear the infection in most patients. However, many survivors suffer from long-term neuronal damage and cannot regenerate all brain functions. HSV-1 influences the physiology of neurons, astrocytes, oligodendrocytes and microglia, and significantly changes their protein expression and secretion pattern. To characterize temporal changes upon HSV-1 infection in detail, we inoculated mixed primary cultures of the murine brain cortex, and performed quantitative mass spectrometry analyses of the cell-associated proteome and the secretome. We identified 28 differentially regulated host proteins influencing inflammasome formation and intracellular vesicle trafficking during endocytosis and secretion. The NIMA-related kinase 7 (NEK7), a critical component of the inflammasome, and ArfGap1, a regulator of endocytosis, were significantly up-regulated upon HSV-1 infection. In the secretome, we identified 71 proteins including guidance cues regulating axonal regeneration, such as semaphorin6D, which were enriched in the conditioned media of HSV-1 infected cells. Modulation of inflammasome activity and intracellular membrane traffic are critical for HSV-1 cell entry, virus assembly, and intracellular spread. Our proteome analysis provides first clues on host factors that might dampen the inflammasome response and modulate intracellular vesicle transport to promote HSV infection of the brain. Furthermore, our secretome analysis revealed a set of proteins involved in neuroregeneration that might foster neuronal repair processes to restore brain functions after clearance of an HSV-1 infection.